Interactive Multimedia Based on Problem-Based Learning for Pancasila Content in Grade IV Elementary School Students - Syebi Ertha Ariani; I Gde Wawan Sudatha; Adrianus I Wayan Ilia Yuda Sukmana (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the less than optimal utilization of digital media, which affects student learning outcomes. This study aims to (1) Analyze the design of interactive multimedia development on Pancasila content for grade IV. (2) Analyze the validity of expert tests on learning content, learning design experts, learning media experts, individual trials, and small group trials on interactive multimedia products on Pancasila content for grade IV Elementary Schools, and (3) Analyze the effectiveness of interactive multimedia on Pancasila content for grade IV Elementary Schools after being used in learning. This research is classified as a type of development research using the ADDIE model. The subjects involved in this study were 3 experts and grade 4 Elementary School students. Data were collected using interview methods, observation, questionnaires and multiple-choice objective tests. Data analysis techniques were qualitative descriptive analysis, quantitative descriptive analysis and inferential statistical analysis (t-test). The study showed very good validation results: subject experts (95.5%), instructional media experts (94%), individual trials (92.44%), and small group trials (94.81%), while instructional design experts rated it good (88.75%). The effectiveness results showed that there was a difference in student learning outcomes after implementing interactive multimedia based on problem based learning on Pancasila content. It was concluded that interactive multimedia based on problem based learning is feasible and effective to be applied to Pancasila content for grade IV Elementary Schools. The innovation of interactive multimedia based on problem based learning has significant implications for the learning process.